Hyperglycemia Increases the Risk of Death in Extremely Preterm Baboons - Blanco, Cynthia L. (2012)
BACKGROUND: Transient neonatal hyperglycemia has been reported in up to 80% of extremely preterm human infants. We hypothesize that severe hyperglycemia (HG) is associated with increased morbidity and mortality in preterm baboons. METHODS: Sixty six baboons born at 67% of gestation were studied. Hyperglycemia was defined as serum glucose level ≥ 150mg/dL during the first week of life. Animals were stratified into 2 groups: severe HG (≥8 events) and non-severe HG (<8 events). RESULTS: Hyperglycemia developed in 65/66 (98%) of the baboons included. A total of 3,386 glucose measurements were obtained. The mean serum glucose level was 159±69 mg/dL for the severe HG group and 130±48 mg/dL for the non-severe HG group during the first week of life. No differences were found in gender, birth weight, sepsis, PDA, or oxygenation/ventilation indices between groups. Severe HG was associated with early death even after controlling for sepsis, postnatal steroid exposure and catecholamine utilization. CONCLUSION: Hyperglycemia is common in preterm baboons and is not associated with short term morbidity. Severe hyperglycemia occurring in the first week of life is associated with early death in preterm baboons.